Ethanol as Dentin Pretreatment on the Bonding Performance of a Two-Step Etch-and-Rinse Adhesive: An In Vivo Study - Silva, Francisco Cláudio Fernandes Alves; Feitosa, Victor Pinheiro; Saboia, Vicente de Paulo Aragão (European Journal of Dentistry, 2019)
Objective The aim of this study was to evaluate the use of 70 vol.% ethanol as a dentin pretreatment on the bond strength (BS) of a two-step etch-and-rinse adhesive.Materials and Methods Resin composite Class I restorations were clinically bonded to acid-etched dentin of human sound third molars using Adper Single Bond 2 (SB, 3M ESPE) and randomly divided into two major groups: dentin saturated with water (control) or 70 vol.% ethanol (ethanol). The teeth were divided into two subgroups: immediately extracted and tested after 24 hours and extraction after 18 months. Bonded teeth (Adper SB 2) were cut into resin–dentin sticks that were tested by microtensile BS, and the failure mode was thereafter evaluated.Statistical Analysis Data were statistically analyzed using two-way analysis of variance and Holm–Sidak post hoc test (α = 0.05). Additional bonded resin–dentin slabs from each group were examined under light microscopy (LM) using the Masson's trichrome staining technique.Results The lowest BS was obtained by ethanol pretreated dentin after aging, while other groups presented similar BS. The LM analysis showed the presence of resin-sparse collagen fibrils in groups examined immediately (24 hours) and the presence of several gaps due to collagen degradation at the interfaces of ethanol pretreated aged specimens (18 months).Conclusion The use of 70 vol.% ethanol in dentin before the application of a two-step etch-and-rinse adhesive should be avoided once it resulted in a significant drop on the BS.
Keywords: bond strength; ethanol wet bonding; hybrid layer